Deteksi awal bayi berat iahir rendah peranan tinggi fundus uteri dan lingkaran lengan atas . - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1990)
AbSTRACT Due to the high incidence rate of the LBW (14% in Indonesia) it is important to conduct early detection. Fundal height, body weight of mothers before pregnancy, increase of body weight during pregnancy, body height, upper arm circumference and the proportion of body weight to body height are important early detection indicators.